Representasi Kebaya Jawa Pada Perempuan Dalam Serial “Gadis Kretek” - Aditian Alam Rizki; Anis Endang SM; Sri Narti (Jurnal Multidisiplin Dehasen (MUDE), 2024)
Research purposes Indonesia, as an archipelagic country with vast cultural diversity, possesses various cultural heritages influenced by many civilizations. Traditional clothing, such as the kebaya, serves as an important symbol of local identity and culture. The film "Gadis Kretek," adapted from a novel by Ratih Kumala, depicts the social realities and struggles of women in the Javanese kretek industry, highlighting traditional kebaya attire as a central element. This research aims to examine the representation of the Javanese kebaya on women in the series "Gadis Kretek" through John Fiske's semiotic analysis. The study employs a descriptive qualitative method with data collection through observation, documentation, and internet searching. The focus of this research is on the first episode of the series. Analysis is conducted on three levels: reality, representation, and ideology. At the reality level, the film portrays life from the colonial era to the independence period with the use of traditional costumes, realistic dialogues, and character behaviors. At the representation level, cinematic techniques such as narration, cinematography, and editing are utilized to construct this reality. At the ideological level, the film conveys values regarding the role of women in the industry, social critique of workers' conditions, and the importance of culture and tradition. The research findings indicate that the film "Gadis Kretek" not only presents an engaging story but also depicts historical realities, reinforces the narrative through cinematic elements, and delivers ideological messages about women's struggles and the significance of cultural heritage. This study is expected to provide insights into cultural representation in mass media and strengthen national cultural identity through the Javanese kebaya.